Longitudinal Doppler Assessments in Late Preterm Fetal Growth Restriction - Mylrea-Foley, Bronacha; Wolf, Hans; Stampalija, Tamara; Lees, Christoph; On behalf of the Truffle-2 Group; TRUFFLE 2 Authors; Arabin, B.; Berger, A.; Bergman, E.; Bhide, A.; Bilardo, C. M.; Breeze, A. C.; Brodszki, J.; Calda, P.; Cetin, I.; Cesari, E.; Derks, J.; Ebbing, C.; Ferrazzi, E.; Ganzevoort, W.; Frusca, T.; Gordijn, S. J.; Gyselaers, W.; Hecher, K.; Klaritsch, P.; Krofta, L.; Lindgren, P.; Lobmaier, S. M.; Marlow, N.; Maruotti, G. M.; Mecacci, F.; Myklestad, K.; Napolitano, R.; Prefumo, F.; Raio, L.; Richter, J.; Sande, R. K.; Thornton, J.; Valensise, H.; Visser, G. H. A.; Wee, L.; TRUFFLE-2 GROUP AND COLLABORATING AUTHORS; C. Brezinka, Department of Obstetrics and Gynecology, Medical University of Innsbruck, Innsbruck, Austria; D. Casagrandi, University College London Hospitals NHS Foundation Trust, London, UK; A. Cerny, Department of Obstetrics and Gynaecology, GeneralUniversity Hospital and First Faculty of Medicine, Charles University, Prague, Czech Republic; A. Dall’Asta, Department of Obstetrics and Gynecology, University of Parma, Parma, Italy; R. DeVlieger, Department of Gynecology and Obstetrics, UZ Leuven, Leuven and Department of Regeneration and Development, KU Leuven, Leuven, Belgium; J. Duvekot, Department of Obstetrics and Gynecology, Erasmus Academic Centre Rotterdam, Rotterdam, The Netherlands; T. M. Eggebo, St Olav’s Hospital, Trondheim, Norway; I. Fantasia, Unit of Fetal Medicine and Prenatal Diagnosis, Institute for Maternal and Child Health, IRCCS Burlo Garofolo, Trieste, Italy; F. Ferrari, Obstetrics & Gynecology, Policlinico University Hospital of Modena, Modena, Italy; N. Fratelli, Department of Obstetrics and Gynecology, ASST Spedali Civili di Brescia and University of Brescia, Brescia, Italy; T. Ghi, Department of Obstetrics and Gynecology, University of Parma, Parma, Italy; O. Graupner, Department of Obstetrics and Gynecology, Klinikum Rechts Der Isar, Technical University of Munich, Munich, Germany; P. Greimel, Department of Obstetrics and Gynecology, Medical University of Graz, Graz, Austria; C. Hofstaetter, Department of Obstetrics & Gynecology, University Hospital of Bern, Bern, Switzerland; D. Lo Presti, Department of Surgery, Division of Obstetrics and Gynecology, Tor Vergata University, Policlinico Casilino Hospital, Rome, Italy; M. Georg, Helsinki University Central Hospital, Helsinki, Finland; F. Macsali, Department of Obstetrics and Gynecology, Haukeland University Hospital, Bergen, Norway; K. Marsal, Department of Obstetrics and Gynecology, Lund University, Skåne University Hospital, Lund, Sweden; P. Martinelli, Department of Neurosciences, Reproductive and Dentistry Sciences, University of Naples ‘Federico II’, Naples, Italy; E. Ostermayer, Department of Obstetrics and Gynecology, Klinikum Rechts Der Isar, Technical University of Munich, Munich, Germany; A. Papageorghiou, Fetal Medicine Unit, St George’s University Hospitals NHS Foundation Trust and Molecular & Clinical Sciences Research Institute, St George’s, University of London, London, UK; R. Peasley, Fetal Medicine Unit, University College London Hospitals NHS Foundation Trust, London, UK; A. Ramoni, Department of Obstetrics and Gynecology, Medical University of Innsbruck, Innsbruck, Austria; L. Sarno, Department of Neurosciences, Reproductive and Dentistry Sciences, University of Naples ‘Federico II’, Naples, Italy; L. Seikku, Helsinki University Central Hospital, Helsinki, Finland; S. Simeone, Department of Health Sciences, University of Florence, Obstetrics and Gynecology, Careggi University Hospital, Florence, Italy; B. Thilaganathan, Fetal Medicine Unit, St George’s University Hospitals NHS Foundation Trust and Molecular & Clinical Sciences Research Institute, St George’s, University of London, London, UK; G. Tiralongo, Department of Surgery, Division of Obstetrics and Gynecology, Tor Vergata University, Policlinico Casilino Hospital, Rome, Italy; A. Valcamonico, Department of Obstetrics and Gynecology, ASST Spedali Civili di Brescia and University of Brescia, Brescia, Italy; C. Van Holsbeke, Department of Obstetrics & Gynaecology, Ziekenhuis Oost-Limburg, Genk, Belgium; A. Vietheer, Department of Obstetrics and Gynecology, Haukeland University Hospital, Bergen, Norway (Ultraschall in der Medizin - European Journal of Ultrasound, 2021)
Purpose To assess the longitudinal variation of the ratio of umbilical and cerebral artery pulsatility index (UCR) in late preterm fetal growth restriction (FGR).Materials and Methods A prospective European multicenter observational study included women with a singleton pregnancy, 32+ 0–36+ 6, at risk of FGR (estimated fetal weight [EFW] or abdominal circumference [AC] < 10th percentile, abnormal arterial Doppler or fall in AC from 20-week scan of > 40 percentile points). The primary outcome was a composite of abnormal condition at birth or major neonatal morbidity. UCR was categorized as normal (< 0.9) or abnormal (≥ 0.9). UCR was assessed by gestational age at measurement interval to delivery, and by individual linear regression coefficient in women with two or more measurements.Results 856 women had 2770 measurements; 696 (81 %) had more than one measurement (median 3 (IQR 2–4). At inclusion, 63 (7 %) a UCR ≥ 0.9. These delivered earlier and had a lower birth weight and higher incidence of adverse outcome (30 % vs. 9 %, relative risk 3.2; 95 %CI 2.1–5.0) than women with a normal UCR at inclusion. Repeated measurements after an abnormal UCR at inclusion were abnormal again in 67 % (95 %CI 55–80), but after a normal UCR the chance of finding an abnormal UCR was 6 % (95 %CI 5–7 %). The risk of composite adverse outcome was similar using the first or subsequent UCR values.Conclusion An abnormal UCR is likely to be abnormal again at a later measurement, while after a normal UCR the chance of an abnormal UCR is 5–7 % when repeated weekly. Repeated measurements do not predict outcome better than the first measurement, most likely due to the most compromised fetuses being delivered after an abnormal UCR.
Keywords: late fetal growth restriction; Doppler; middle cerebral artery; brain sparing; adverse outcome